Initiating meaningful social interactions in a high-immersion self-access language learning space - Jauregi-Ondarra, Kristi; Christoforou, Maria; Boglou, Dimitrios (My University, 2022)
Virtual Reality (VR) has paved the way for learner interaction in immersive environments, simulating authentic cultural conditions in the target language and encouraging collaborative opportunities. This article describes how the high-immersion VR social application AltspaceVR served as an immersive Self-Access Language Learning (SALL) space in a collaborative online international learning (COIL)
Keywords: Self-Access Language Learning (SALL); Collaborative Online International Learning (COIL); Social High Immersion; Virtual Reality; Telecollaboration